Stablecoins in the System of Current Russian Legislation - L. A. Novoselova (Цифровое право, 2025)
The relevance of this research lies in the need to comprehend the legal implications of the development of stablecoins as new financial instruments. Faced with the processes of digitalization, legal systems have been required to develop a response to the significant changes to the techniques of undertaking domestic and crossborder transactions and settlements. In particular this concerns the emergence of the possibility of direct transactions between counterparties, bypassing the classical financial institutions. The emergence of new, digital objects with an unspecified legal regime (cryptocurrencies, utility tokens, etc.) has also led to problems. Stablecoins are one of the most frequently used objects. They are a type of digital asset accepted in transactions at a predetermined (determined) value (rate). The aim of the research is to establish potential strategies for incorporating stablecoins in Russian civil law as objects of legal rights. For this purpose, the article discusses the approaches of foreign regulators when selecting a model for regulating relations with such assets. It notes that they are characterised by a pragmatism which allows the rules developed for known objects (securities, exchange commodities, etc.) to be extended to different types of stablecoins for a variety of purposes. In the Russian Federation, the formation of a legal environment for the circulation of digital assets, including those which possess the features of stablecoins, is still at an early stage. The main legislative acts, including the Civil Code of the Russian Federation, only address the issue of instruments created and traded on domestic, Russian platforms. An analysis of the Law on Digital Financial Assets and the Law on Attraction of Investments shows that many of the digital rights defined therein are similar in nature to stablecoins. They can be either secured (utilitarian rights, a number of DFAs), or unsecured (digital currency with a fixed value). However, Russian legislation, including the Law on Currency Regulation, does not refer to and, therefore, does not regulate relations with the use of “external” stablecoins. The need to introduce “external” stablecoins into the Russian legal framework, including for use in foreign trade transactions, requires changes to the legislation and regulatory approach. The article analyzes recent legislative changes and legislative initiatives in the field of digital rights regulation, and suggests ways of removing existing gaps and inconsistencies.